2019
DOI: 10.1016/j.eurox.2019.100054
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after laparoscopic removal of Essure® sterilization devices

Abstract: Objective(s) To assess changes in quality of life after laparoscopic removal of Essure ® sterilization devices (Bayer AG, Leverkusen, Germany). Study Design In this prospective observational study in an academic research hospital, 80 women with new or worsening symptoms since placement of Essure ® sterilization devices undergoing subsequent surgical removal were included. Laparoscopic removal of Essure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It is not certain that these potential toxic metals are necessarily responsible for the adverse effects. As a result, there are no indications to date to remove implants to all patients, especially in case of non-symptomatic patients [1]. In symptomatic patients, there are also no biological or clinical arguments to prefer hysterectomy with salpingectomy rather than laparoscopic conservative procedure (salpingectomy with traction on the implant or salpingectomy with mini-cornuectomy) [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not certain that these potential toxic metals are necessarily responsible for the adverse effects. As a result, there are no indications to date to remove implants to all patients, especially in case of non-symptomatic patients [1]. In symptomatic patients, there are also no biological or clinical arguments to prefer hysterectomy with salpingectomy rather than laparoscopic conservative procedure (salpingectomy with traction on the implant or salpingectomy with mini-cornuectomy) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Since the decision to halt sales of the Essure® implants for permanent birth control in December 2018 (Bayer©, Leverkusen, Germany), many patients have complained of unspecific symptoms, such as gynecological disorders (pain, menorrhagia), but also broad extrapelvic symptoms (persistent asthenia and fatigue, heart palpitations, tinnitus, pruritus, joint and / or muscularis pain, skin rashes, digestive disorders) [1]. Several studies have shown an improvement in symptomatology and quality of life after Essure® removal in symptomatic patients [1,2]. The question arises as to what is the pathophysiology of these local and systemic adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that the incision and traction method poses more technical difficulties than the cornuectomy approach. 23 Surgeons reported significant difficulty controlling the tensile pressure with traction, whereas use of the cornuectomy approach eliminated this risk and decreased the risk of fragmentation and incomplete removal. 23,24 Charavil and colleagues demonstrated in a prospective observational study that a vaginal hysterectomy with bilateral salpingectomy is a feasible approach to Essure removal.…”
Section: The Timing and Onset Of Pelvic Pain Vary Widely Aftermentioning
confidence: 99%
“…Several studies have demonstrated an improvement of symptomatology and quality of life after removal of the Essure ® device in symptomatic patients ( 1 , 2 ). The pathophysiology of adverse effects related to the device may be explained by the release of heavy metals from a possible corrosion of the implant ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of adverse effects related to the device may be explained by the release of heavy metals from a possible corrosion of the implant ( 3 ). Therefore, because there is a risk of fracture in up to 30% of cases ( 2 ), the implant should be removed completely and safely ( 4 ). Our aim was to give a step-by-step description of an easy surgical technique with a demonstrative video.…”
Section: Introductionmentioning
confidence: 99%